2021
DOI: 10.2139/ssrn.3785919
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bullying on Academic Performance: A Case Study for the Community of Madrid

Abstract: Bullying is a problem that affects children and teenagers around the world and its repercussions can endure throughout adult life. Its prevalence is, in part, a product of the lack of information and the paucity of studies which analyse the wideranging consequences for the individuals involved. The main objective of this research is to study the incidence of bullying on the academic performance of students in education centres in the Madrid Region. The databases used are those of Competency Tests carried out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Collaborative efforts between school psychologists and teachers can empower students, promoting social justice and ensuring they are aware of their rights. Previous studies have indicated that bullying victimization has a direct negative impact on students’ academic performance and social interactions (Huang, 2022; Rusteholz et al, 2021). In this study, the author argues that students from minority backgrounds experience higher rates of online victimization, as well as online and offline discrimination compared to their Farsi-speaking counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative efforts between school psychologists and teachers can empower students, promoting social justice and ensuring they are aware of their rights. Previous studies have indicated that bullying victimization has a direct negative impact on students’ academic performance and social interactions (Huang, 2022; Rusteholz et al, 2021). In this study, the author argues that students from minority backgrounds experience higher rates of online victimization, as well as online and offline discrimination compared to their Farsi-speaking counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Every student deserves to thrive in a safe school and classroom free from bullying. Rusteholz et al (2021) suggested that classroom environments characterised by caring staff attitudes, peer friendships and acceptance are protective against school bullying. Ratib & Lisa (2021) posits that learners with disabilities are less vulnerable to bullying in schools where teachers actively encourage and facilitate peer relationships and positive interactions between students with and without disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Factors that increase vulnerability include the 'closed' nature of institutions, inadequate inspection and lack of accountability. Rusteholz et al (2021) revealed school bullying adversely affects the education of learners with disabilities. The increasing burden of bullying, on children with disabilities coming from their peers and teachers usually forced them to come late or drop out of schools (Allam & Martin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of bullying is greater on the victims, although its impact also reaches the aggressors and spectators (Íñiguez Berrozpe et al 2020;Rusteholz et al 2021) The sequelae have effects both within the school environment, as well as on physical and mental health and not only while they are living the experience but can last throughout adult life (Rusteholz et al 2021). As protective factors, having an adequate positive social environment formed by family and friends stands as support in defense against victimization (Lee et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to academic performance, empirical evidence shows the probability of low academic performance associated with subject failure when school bullying is persistent (Rusteholz et al 2021). An optimal relationship with teachers affects school performance (Chamizo-Nieto et al 2021).…”
Section: Introductionmentioning
confidence: 99%